MSMES’ PERCEPTIONS OF THE DEVELOPMENT OF THE PADANG-PEKANBARU TOLL ROAD (PAYAKUMBUH-PANGKALAN SECTION) - Eriza Nazaruddin; Weriantoni; Nadia Tul Aisyah; Hutrisia Marafikha Afwa (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
It is hoped that the Padang - Pekanbaru Toll Road can boost economic growth in the surrounding area and can support achieving economic growth of 7% in the next years and economic growth in developing regional potential and Micro, Small and Medium Enterprises (MSMEs). In particular, West Sumatra province has a lot of MSMEs, so it is hoped that this can improve the welfare of MSMEs. However, with the construction of the Padang-Pekanbaru Toll Road, will the marketing strategy of MSMEs change in the future? So this research aims to see how MSMEs, especially Sanjai MSMEs in Payakumbuh City, perceive the toll road construction. The research method is quantitative descriptive with saturated sampling techniques. The results of this research are that Sanjai MSMEs in Payakumbuh City perceive that there will certainly be a positive impact in the form of less congestion and easy access to connectivity between cities, while the negative impact of the existence of toll roads will make people prefer to use toll roads rather than inner city roads, which can cause Sanja MSMEs to experience the decline in sales is even feared that they could lose market share.